2022
DOI: 10.1039/d1qo01841h
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light enabled photochemical reduction of 1,2-dicarbonyl compounds by Hünig's base

Abstract: Here, we report a visible-light enabled platform for the photochemical reduction of 1,2-dicarbonyl compounds to α-hydroxy carbonyl derivatives which utilizes diisopropylethylamine (Hünig’s base) as a reductant. This reaction tolerates a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…In the case of benzil, benzoin was isolated as the major product (not shown). 11 Based on these results, we speculate that the spatial configuration of 1,2-diones plays a vital role in the transformation. It worth noting that the rigid phenanthrene-based planar molecular frameworks of α-hydroxy ketones provide a versatile platform for further functionalization.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…In the case of benzil, benzoin was isolated as the major product (not shown). 11 Based on these results, we speculate that the spatial configuration of 1,2-diones plays a vital role in the transformation. It worth noting that the rigid phenanthrene-based planar molecular frameworks of α-hydroxy ketones provide a versatile platform for further functionalization.…”
mentioning
confidence: 95%
“…This reagent offers significant advantages over traditional XAT transfer reagents, such as Mn·, Sn·, and Si·, due to its low toxicity and cost-effectiveness. Our recent experiments have shown that both α-aminoalkyl and ketyl radicals can be formed in a single process via a visible light photochemical hydrogen atom transfer (HAT) process between 1,2-diketones and trialkyl amines (Scheme b) . Based on these findings, we hypothesized that the carbonyl addition reaction could be achieved via the coupling reaction of ketyl radicals and carbon radicals (formed from α-aminoalkyl radical promoted XAT process) by directly utilizing organic halides, as shown in Scheme c.…”
mentioning
confidence: 99%
See 3 more Smart Citations